2008
DOI: 10.1002/ar.20762
|View full text |Cite
|
Sign up to set email alerts
|

The Source of Carbon Dioxide for Gastric Acid Production

Abstract: The source of carbon dioxide for the chemical reaction leading to the production of gastric acid is unknown. The decarboxylation of an amino acid releases carbon dioxide. Pepsinogens provide a rich source of the amino acid arginine. Both the source of carbon dioxide, arginine, and the consequence of arginine decarboxylation, agmatine, have been studied. The site of carbon dioxide production has been related to the survival of the parietal cell. An immunohistochemical study has been carried out on glycol methac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The trend of the changes in CO 2 defined by the gastric gas profiler is similar to that obtained from measurements in a respiration chamber 43 44 , indicating that the gastric CO 2 production is mainly attributable to the chemical reactions in the acidic environment of the stomach 45 . This is also likely to be accompanied by products of aerobic metabolism of amino acids obtained from protein digestion, which are then chemically decarboxylated into CO 2 gas 46 . The concomitant rise in gastric temperature is likely to be attributed to metabolic heat generation from the chemical reaction as a result of the protein digestion 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend of the changes in CO 2 defined by the gastric gas profiler is similar to that obtained from measurements in a respiration chamber 43 44 , indicating that the gastric CO 2 production is mainly attributable to the chemical reactions in the acidic environment of the stomach 45 . This is also likely to be accompanied by products of aerobic metabolism of amino acids obtained from protein digestion, which are then chemically decarboxylated into CO 2 gas 46 . The concomitant rise in gastric temperature is likely to be attributed to metabolic heat generation from the chemical reaction as a result of the protein digestion 47 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, this is confirmed by the rise in gastric pH and the reduction of pepsin seen in the Raman spectrum. Such a reduction of gastric acid and pepsin secretion eventually leads to a lowered gastric CO 2 and metabolic heat production, because gastric CO 2 is mainly produced from the chemical reaction of food in an acidic environment together with the decarboxylation of amino acids upon protein digestion 45 46 . These are all related to the concentrations of both gastric acid and pepsin.…”
Section: Discussionmentioning
confidence: 99%
“…This includes several members of the Rab family of GTPases [ 23 ], SNARE proteins and secretory carrier membrane proteins. In addition to a regulatory influence on the vesicle transport it is tempting to speculate, that AZIN2 locally activates ODC that by decarboxylation of ornithine generates CO2 and hereby provides CO2 required for production of gastric acid [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the live mouse, for example, the partial O 2 pressure (pO 2 ) in the stomach is estimated at 58 Ϯ 15 torr (ϳ7.6%) (20). O 2 and CO 2 concentrations are variable within the gastric environment and can be affected by disease state, food consumption, and location within the gastric mucosa (21,22). For example, the CO 2 concentration tends to be low nearest the epithelium (where the pH is high) and higher toward the gastric lumen (where the pH is low).…”
mentioning
confidence: 99%